FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MANAJEMEN LAKTASI PADA IBU MENYUSUI DI PMB ROSIDA HIMAWATI - Nurma Ika Zuliyanti; Yusti Syah Putri; Ayu Amalia Anggraeni (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah (LRPMPI), 2026)
Lactation management encompasses all efforts made to assist mothers in successfully breastfeeding their infants. These efforts are particularly crucial during the exclusive breastfeeding period, defined as the first 0–6 months postpartum. A preliminary study conducted at the Independent Midwifery Practice (PMB) of Rosida Himawati, S.S.T., Bdn, between January and September 2025, identified 135 breastfeeding mothers with infants aged 0–2 years; of these, 123 were breastfeeding, while 12 were not (comprising housewives, entrepreneurs, civil servants, farmers, and laborers). The study aimed to identify factors associated with lactation management among breastfeeding mothers at this practice in the Tambakrejo area, Purworejo District. An analytic observational study design with a cross-sectional approach was employed. The study population consisted of all breastfeeding mothers attending the practice. Total sampling was used, and data were analyzed using the Chi-square test. Results indicated significant associations (p < 0.05) for the variables of knowledge (p = 0.018), family support (p = 0.02), and income (p = 0.001). No significant associations were found regarding education (p = 0.825), place of delivery (p = 0.403), occupation (p = 0.774), or age (p = 0.997). Husbands and family members are encouraged to provide emotional support, information, and assistance with maternal care during the breastfeeding period. Optimal family support boosts maternal confidence and facilitates successful lactation management.